[Afisz. Incipit] Rolnicy wymieniajcie nasiona zbóż! (Malbork : [wydawca nieznany], 1954)
Afisz informujący o możliwości wymiany nasion.
Keywords: Malbork (Polska ; region) -- 1945-1970 -- druki ulotne; Gmina Malbork (woj. pomorskie, pow. malborski); Druki ulotne -- 1945-1970.; Druki ulotne